Jawabanmu

2014-03-13T11:25:38+07:00
a.1/3×-5=10
   1/3x = 10 + 5
   1/3x = 15
       x = 15 . 3/1
       x = 45
b.3/4×-1/5×=2
   15/20x - 4/20x = 2
   11/20x =2
           x = 2 . 20/11
           x = 40/11

a.×/2=×/5-10
   x/2 - x/5 = -10
  5x/10 - 2x/10 = -10
   3x/10 = -10
         x = -10 . 10/3
         x = -100/3
b.6/×-3/×=15/4

   -3/x = 15/4
       x = 15/4 . -1/3
       x = -15/12
       x = -5/4
a.1/3×-5=10
1/3x = 10 + 5
1/3x = 15
x = 15 . 3/1
x = 45
b.3/4×-1/5×=2
15/20x - 4/20x = 2
11/20x =2
x = 2 . 20/11
x = 40/11

a.×/2=×/5-10
x/2 - x/5 = -10
5x/10 - 2x/10 = -10
3x/10 = -10
x = -10 . 10/3
x = -100/3
b.6/×-3/×=15/4
-3/x = 15/4
x = 15/4 . -1/3
x = -15/12
x = -5/4
2014-03-13T11:27:59+07:00
a.1/3×-5=10
   1/3x = 10 + 5
   1/3x = 15
       x = 15 . 3/1
       x = 45
b.3/4×-1/5×=2
   15/20x - 4/20x = 2
   11/20x =2
           x = 2 . 20/11
           x = 40/11

a.×/2=×/5-10
   x/2 - x/5 = -10
  5x/10 - 2x/10 = -10
   3x/10 = -10
         x = -10 . 10/3
         x = -100/3
b.6/×-3/×=15/4

   -3/x = 15/4
       x = 15/4 . -1/3
       x = -15/12
       x = -5/4